Association between the development of bronchopulmonary dysplasia and platelet transfusion: a protocol for a systematic review and meta-analysis - Chioma, Roberto; Ghirardello, Stefano; Włodarczyk, Krzysztof; Ulan-Drozdowska, Joanna; Spagarino, Antonio; Szumska, Marta; Krasuska, Klaudia; Seliga-Siwecka, Joanna; Philip, Roy K.; Al Assaf, Niazy; Pierro, Maria (Frontiers in Pediatrics, 2023)
Background: There is a lack of consensus on the management of thrombocytopenia in preterm infants, and the threshold for prophylactic platelet transfusion varies widely among clinicians and institutions. Reports in animal models suggested that platelets may play a relevant role in lung alveolarization and regeneration. Bronchopulmonary dysplasia (BPD) is a severe respiratory condition with a multifactorial origin that affects infants born at the early stages of lung development. Recent Randomized-Controlled Trials (RCTs) on the platelets count threshold for prophylactic transfusions in preterm infants with thrombocytopenia suggest that a higher exposition to platelet transfusion may increase the risk of BPD. Here, we report a protocol for a systematic review, which aims to assist evidence-based clinical practice and clarify if the administration of platelet products may be associated with the incidence of BPD and/or death in preterm infants. Methods: MEDLINE, Embase, Cochrane databases, and sources of grey literature for conference abstracts and trial registrations will be searched with no time or language restrictions. Case-control studies, cohort studies, and non-randomized or randomized trials that evaluated the risk for BPD and/or death in preterm infants exposed to platelet transfusion will be included. Data from studies that are sufficiently similar will be pooled as appropriate. Data extraction forms will be developed a priori. Observational studies and non-randomized and randomized clinical trials will be analyzed separately. OR with 95% CI for dichotomous outcomes and the mean difference (95% CI) for continuous outcomes will be combined. The expected heterogeneity will be accounted for using a random-effects model. Subgroup analysis will be performed based on a priori-determined covariate of interest. In case of sufficient homogeneity of interventions and outcomes evaluated, results from subgroups of studies will be pooled together in a meta-analysis. Discussion: This systematic review will investigate the association of BPD/death with platelets components administration in preterm infants, and, consequently, it will provide reliable indications for the evidence-based management of premature patients with thrombocytopenia.